Osteoid Osteoma of the Trapezium: Case Report of an Unusual Tumor Location Presenting a Diagnostic Challenge - S. E. Roberts; M. N. Mirzabeigi; A. Naik; C. Preciado; B. Chang (Case Reports in Orthopedics)
Osteoid osteoma is a benign bone tumor, which represents approximately 10% of all benign bone tumors. When localized to the carpus, osteoid osteomas are most often seen in the scaphoid and capitate. Rarely, these tumors can also be observed in the trapezium. Given the infrequency with which osteomas are located in the trapezium and often nonspecific presenting symptoms, diagnosis of this tumor can be challenging and requires a high index of suspicion.